2009
DOI: 10.1111/j.1752-1688.2009.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Bankfull Regional Curves for North and Northwest Florida Streams1

Abstract: Regional curves, which relate bankfull channel dimensions and discharge to watershed drainage area, are developed to aid in identifying the bankfull stage in ungaged watersheds, and estimating the bankfull discharge and dimensions for river studies and natural channel design applications. This study assessed 26 stable stream reaches in two hydro‐physiographic regions of the Florida Coastal Plain: the Northwest Florida Coastal Plain (NWFCP) and the North Florida Coastal Plain (NFCP). Data from stream reaches in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Developing a stream restoration design, such as through natural channel design techniques, is an iterative process that often begins by identifying the appropriate bankfull discharge and bankfull channel dimensions such as cross‐sectional area, width, and mean depth in the riffles, predominately in perennial streams, with the aid of regional curves (Doll et al ., ; Hey, ; USDA‐NRCS, ). Regional curves relate these bankfull channel characteristics ( i.e ., dependent variable) to drainage area ( i.e ., independent variable) and can provide designers with (1) tools to help identify bankfull elevation in the field such as when bankfull indicators are absent or infrequent (Castro and Jackson, ; Metcalf et al ., ; Brockman et al ., ) and (2) a basis for stream assessment and design (Hey, ; USDA‐NRCS, ). Similar to hydraulic geometry curves (Leopold and Maddock, ), regional curves (Dunne and Leopold, ) are of the form:Qnormalbkf=aAwbAnormalbkf=cAwdWnormalbkf=gAwhDnormalbkf=jAwkThe variable A w represents drainage area (km 2 ), Q bkf is bankfull discharge (m 3 /s), A bkf is bankfull cross‐sectional area (m 2 ), W bkf is bankfull width (m), D bkf is bankfull mean depth (m), and the coefficients a , c , g , and j as well as the exponents b , d , h , and k are empirically derived values used to fit the data (Dunne and Leopold, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing a stream restoration design, such as through natural channel design techniques, is an iterative process that often begins by identifying the appropriate bankfull discharge and bankfull channel dimensions such as cross‐sectional area, width, and mean depth in the riffles, predominately in perennial streams, with the aid of regional curves (Doll et al ., ; Hey, ; USDA‐NRCS, ). Regional curves relate these bankfull channel characteristics ( i.e ., dependent variable) to drainage area ( i.e ., independent variable) and can provide designers with (1) tools to help identify bankfull elevation in the field such as when bankfull indicators are absent or infrequent (Castro and Jackson, ; Metcalf et al ., ; Brockman et al ., ) and (2) a basis for stream assessment and design (Hey, ; USDA‐NRCS, ). Similar to hydraulic geometry curves (Leopold and Maddock, ), regional curves (Dunne and Leopold, ) are of the form:Qnormalbkf=aAwbAnormalbkf=cAwdWnormalbkf=gAwhDnormalbkf=jAwkThe variable A w represents drainage area (km 2 ), Q bkf is bankfull discharge (m 3 /s), A bkf is bankfull cross‐sectional area (m 2 ), W bkf is bankfull width (m), D bkf is bankfull mean depth (m), and the coefficients a , c , g , and j as well as the exponents b , d , h , and k are empirically derived values used to fit the data (Dunne and Leopold, ).…”
Section: Introductionmentioning
confidence: 99%
“…Developing a stream restoration design, such as through natural channel design techniques, is an iterative process that often begins by identifying the appropriate bankfull discharge and bankfull channel dimensions such as cross-sectional area, width, and mean depth in the riffles, predominately in perennial streams, with the aid of regional curves (Doll et al, 2003;Hey, 2006;USDA-NRCS, 2007). Regional curves relate these bankfull channel characteristics (i.e., dependent variable) to drainage area (i.e., independent variable) and can provide designers with (1) tools to help identify bankfull elevation in the field such as when bankfull indicators are absent or infrequent (Castro and Jackson, 2001;Metcalf et al, 2009;Brockman et al, 2012) and (2) a basis for stream assessment and design (Hey, 2006;USDA-NRCS, 2007). Similar to hydraulic geometry curves (Leopold and Maddock, 1953), regional curves (Dunne and Leopold, 1978) are of the form:…”
Section: Introductionmentioning
confidence: 99%
“…Metcalf et al [44] also found bankfull return intervals in these ranges for the northern regions of Florida. Such return intervals also agree with values found by stream restoration practitioners working in the Inner Bluegrass and Outer Bluegrass [59].…”
Section: Bankfull Return Intervalsmentioning
confidence: 92%
“…Figure shows the MD Coastal Plain from this study compared to other Coastal Plain regions, including VA, North Carolina, and Florida (FL). Interestingly, the FL curves (Metcalf et al ., ) are the most different. FL receives more rainfall than the other regions, which may explain why the Northwest FL curve is the highest.…”
Section: Comparisons To Other Curvesmentioning
confidence: 99%